The philosopher, or on faith - Amoiroutzēs, Georgiōs, 1400-1470. (Washington, DC)
xi, 237 sayfa
Keywords: “'God necessarily exists, since it is not possible for things to be otherwise, as Aristotle shows in the Metaphysics.' So Mehmed II, the Ottoman conqueror of both Constantinople and Trebizond, tells George Amiroutzes, the Byzantine scholar and native of Trebizond, in the beginning of Amiroutzes' dialogue The Philosopher, or On Faith. The dialogue is a literary recreation of the conversations between Mehmed, a Muslim, and Amiroutzes, a Christian. In the course of The Philosopher, the two debate the role of logic and rationality in religious debate, the nature of God, and the fate of the body and soul in the afterlife. Surprisingly complex and subtle arguments emerge, firmly situated in their fifteenth-century context but steeped in the long Greek philosophical tradition. Previously known only from a sixteenth-century Latin translation, The Philosopher was recently rediscovered in a Greek manuscript in Toledo. In this volume, John Monfasani presents both the editio princeps of this manuscript and the first translation of the text from the Greek, with an introduction that discusses the life of Amiroutzes and the text as well as two appendixes that offer texts and translations of two additional documents related to Amiroutzes and The Philosopher.“ --